Teachers’ religious coping in Malaysia: scale validation - Ismail, Zanariah; Abdullah, Ssekamanya Siraje (Association of Malaysian Muslim Intellectuals, 2013)
Studies on the ideas of previous muslim scholars can give some insight for the contemporary educational practices. Ibn Sahnun was among the pioneer in the field of Islamic Education. This study aims to analyse and interpret the ideas of Ibn Sahnun in relation to education, and the relevance of his ideas to the current educational system. Also, to determine whether his ideas could be implemented in contemporary educational system. The study employed content analysis methodology using his work in the field of education namely Adab al-Mu’allimin (Rules of Conduct for Teachers). It was found that the ideas of Ibn Sahnun’s on Islamic education could be divided into three major categories. Teaching al-Quran is the compulsory subject that must be offered by educational institution. Ibn Sahnun has given particular concerns on the lower primary education. The researchers suggested teachers professional ethics must be seriously observed by teachers as well as teaching al-Quran must be a major concern by modern educational system.